LICHENS AS BIOINDICATORS IN FRESHWATER ECOSYSTEMS - CHALLENGES AND PERSPECTIVES - Nascimbene, J.; Nimis, P. L.; Thüs, H. (Annali di Botanica, 2013)
This paper summarizes information on freshwater lichens in relation with their potential for bioindication, mainly pointing to ecological concepts and issues of practical relevance for promoting their inclusion in routine biomonitoring practices, thus contributing to a full implementation of the EU Water Framework directive. Results highlight the sensitiveness of freshwater lichens to some factors which cannot be technically measured by singular visits, and have relevance for human planning purposes and environmental impact and risk assessment. However, a full inclusion of freshwater lichens in monitoring practices would benefit from further ecological research testing the influence of potentially meaningful ecological drivers and developing statistically robust sampling methods. This would allow the development of standard guidelines applicable across Europe according to the policies of the EU Water Framework directive. On the taxonomical side, further DNA-based revisions and the creation of a European checklist of freshwater lichens, should provide the basis for developing modern identification tools. Finally, it is suggested that the use of freshwater lichens in biomonitoring may be improved by model studies based on comparative trials of full, quantitative, species inventories at different spatial scales and by parallel simplified approaches with selected indicator species and morphological groups.